EFEKTIFITAS METODE PEMBELAJARAN JOYFULL LEARNING DALAM MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS II SDN 7 KECAPI - Rahmah, Nafisatur; Hamidaturrohmah, Hamidaturrohmah (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Education has a very important role in making the nation's life intelligent, but learning models that are less varied will cause students to be less able to read. Based on the problems above, the implementation of this research aims to improve critical thinking skills through the joy learning method in improving the reading skills of class II students at SD Negeri 7 Kecapi. This research is quantitative with a One-Groub Pretest Posttest model. Technical analysis uses Normality Test, Homogeneity, Simple Regression Test, Anova Test, R-Square Determination Test and T Test. The population and sample in class II are 12 students. The research results showed that the average pretest score was 76.50 and the posttest score was 87.08. Hypothesis testing in the form of t tests and simple regression also shows a significant influence on critical thinking skills.